2021
DOI: 10.1111/jcal.12574
|View full text |Cite
|
Sign up to set email alerts
|

The pandemic semesters: Examining public opinion regarding online learning amidst COVID‐19

Abstract: The current educational disruption caused by the COVID-19 pandemic has fuelled a plethora of investments and the use of educational technologies for Emergency Remote Learning (ERL). Despite the significance of online learning for ERL across most educational institutions, there are wide mixed perceptions about online learning during this pandemic. This study, therefore, aims at examining public perception about online learning for ERL during COVID-19. The study sample included 31,009 English language Tweets ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The impact of COVID-19 on education has created an urgent need to evaluate the opinion of distance learning ever than before especially due to the wide mixed perception towards remote learning. Public opinion on the use of Emergency Remote Learning (ERL) was analyzed using the data collected from Twitter (Asare et al 2021 ). The study was able to detect positive and negative sentiments and revealed topics for each of the clusters thus serving as a recommendation to improve the online educational systems amidst the pandemic.…”
Section: Related Workmentioning
confidence: 99%
“…The impact of COVID-19 on education has created an urgent need to evaluate the opinion of distance learning ever than before especially due to the wide mixed perception towards remote learning. Public opinion on the use of Emergency Remote Learning (ERL) was analyzed using the data collected from Twitter (Asare et al 2021 ). The study was able to detect positive and negative sentiments and revealed topics for each of the clusters thus serving as a recommendation to improve the online educational systems amidst the pandemic.…”
Section: Related Workmentioning
confidence: 99%
“…The following problems have been studied in selected PRISMA research papers: Higher education quality assurance ( Alakbarov 2021 ; Allayarova 2019 ; Asare et al 2021 ); Knowledge-based recommender system ( Barabash et al 2021 ; Barón et al 2015 ; Bin-Noor et al 2021 ; Brunello and Wruuck 2021 ); E-learning and distance learning ( Bukralia et al 2015 ; Burman et al 2021 ; Casselman 2021 ; Chahal et al 2020 ); Inter-professional education ( Cheng 2017 ); Network course recommendation system ( Cinquin et al 2019 ; Dhar and Jodder 2020 ; Dolgikh 2021 ; Ehimwenma and Krishnamoorthy 2021 ); Modern information communication technologies in the higher education sector ( El Gourari et al 2021 ; Elahi et al 2022 ; Ellyatt 2021 ; Elumalai et al 2019 ); Transformation of education during the COVID-19 pandemic ( Erridge 2006 ; Ezz and Elshenawy 2020 ; Fedushko and Ustyianovych 2020 ); Digitalization in higher education ( Gao et al 2021 ; Garay-Jiménez et al 2021 ; Gil et al 2019 ); Personalized recommendation system for learning resources ( Habib et al 2021 ; Ibrahim et al 2019 ; Karan and Asgari 2021 ; Khan and Ramzan 2018 ; Khosravi et al 2021 ); Artificial intelligence techniques for education tasks solving ( Kim Rosemary et al 2014 ; ...…”
Section: Literature Reviewmentioning
confidence: 99%
“…Against the background of the COVID-19 pandemic, online learning has become a vital alternative learning mode worldwide [1,2]. As learners and instructors have been separated physically, the convenience and flexibility of online environments have guaranteed basic educational needs [3,4]. However, the socially isolated features of online learning settings have also caused challenges for instructors in monitoring their learners' progress and in identifying learners who are at risk [5].…”
Section: Introductionmentioning
confidence: 99%